2009
DOI: 10.1007/s10549-009-0473-3
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and mechanism of action of a new ROS-generating microsphere formulation for circumventing multidrug resistance in breast cancer cells

Abstract: Multidrug resistance (MDR) is one of the main challenges in the treatment of breast cancer. A new microsphere formulation able to generate reactive oxygen species (ROS) locally was thus investigated for circumventing MDR in breast cancer cells in this work. Glucose oxidase (GOX) was encapsulated in alginate/chitosan hydrogel microspheres (ACMS-GOX). The in vitro cytotoxicity of ACMS-GOX to murine breast cancer EMT6/AR1.0 cells, which overexpress P-glycoprotein (P-gp), was evaluated by a clonogenic assay. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 45 publications
0
28
0
Order By: Relevance
“…Our mechanistic study, using various extracellular reactive oxygen metabolite scavengers and intracellular antioxidant enzyme inhibitors and iron chelators, indicated that extracellular H 2 O 2 and . O 2 − played a more important role in the cytotoxicity of ACMS-GOX than FR-GOX, and that ·OH is the major ROS accounting for intracellular cytotoxicity (14). As cellular uptake of GOX was not detectable, either upon incubation with FR-GOX or ACMS-GOX and OH has a very short half life (14), it is likely that the intracellular OH was produced inside the cells by H 2 O 2 that is generated outside and then diffuses into the cells.…”
Section: Cytotoxicity Of Fr-gox and Acms-gox To Breast Cancer Cellsmentioning
confidence: 96%
See 4 more Smart Citations
“…Our mechanistic study, using various extracellular reactive oxygen metabolite scavengers and intracellular antioxidant enzyme inhibitors and iron chelators, indicated that extracellular H 2 O 2 and . O 2 − played a more important role in the cytotoxicity of ACMS-GOX than FR-GOX, and that ·OH is the major ROS accounting for intracellular cytotoxicity (14). As cellular uptake of GOX was not detectable, either upon incubation with FR-GOX or ACMS-GOX and OH has a very short half life (14), it is likely that the intracellular OH was produced inside the cells by H 2 O 2 that is generated outside and then diffuses into the cells.…”
Section: Cytotoxicity Of Fr-gox and Acms-gox To Breast Cancer Cellsmentioning
confidence: 96%
“…glucose oxidase (GOX), have been investigated for treatment of tumors (11,12). GOX, which generates hydrogen peroxide in the presence of oxygen and glucose, has been shown to exhibit antitumor activity both in vitro and in vivo under physiological conditions (11)(12)(13)(14) and efficacy in overcoming MDR in breast cancer cells (13,14). Because GOX is susceptible to degradation and denaturation, daily intratumoral injection of GOX was applied to inhibit tumor growth in vivo (11).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations